Multimedia Pembelajaran Mixed Media dan Kolaborasi - Rachman, Anung (Institut Seni Indoensia Surakarta, 2009)
The role of education world always must be dynamic and listens carefully in facing and anticipates all changes in happened. Some problems experienced by teacher in process of pure art study at university with material scope Mixed Media and collaboration is the subject difficult to be comprehended without in backing with media because teacher in giving lesson still conventionally, and instructor which has not so mastering is information technology, and curriculum now is delivered university autonomy causing teacher is claimed to makes method and strategy in teaching Study model applied in research to distinguish computer by using Adobe Flash is being based on Multimedia with approach of the constructivism theory in overcoming study problems of pure art.This paper describes the process of making multimedia learning, concept, design, until programming. In the end section also described the results of produce including an analysis of the multimedia learningÂ Keyword : mixed media and collaboration, Multimedia, learning